Social justice in gender relations : regional inequalities and socioeconomic status of women in Croatia - Klasnić, Ksenija, sociologinja; Weisglass, Maja (2013)
The purpose of our presentation was to outline the gender issues in Croatia, which reflect the problems of transition, social justice, inequality and mobility in the context of global trends of neoliberal capitalism and are a good example of how macrostructural patterns and problems reflect the everyday life and interpersonal relationships. The main goal of this presentation was to offer a new way of measuring the socioeconomic status of women in intimate relationships, as well as to present the results of a survey research conducted in the year 2012 on a representative sample of women who live with their partners. The results were contextualized by emphasizing the regional differences in socioeconomic status of women, but also describing the perception of the major social problems in different regions of Croatia.
ENG